Integrated Pharmaceutics - Applied Preformulation, Product Design, and Regulatory Science (2nd Edition) - Al-Achi, Antoine; Gupta, Mali Ram; Stagner, William Craig (John Wiley & Sons, 2023)
Pharmaceutics refers to the subfield of pharmaceutical sciences that develops drug delivery products or devices to optimize the drug's performance once administered. This multidisciplinary field draws on physical chemistry, organic chemistry, and biophysics to generate and refine these crucial elements of medical care. Moreover, incorporating such disparate dimensions of drug product design as material properties and legal regulation bridges the gap between effective chemicals and viable medical treatments. Integrated Pharmaceutics provides a comprehensive introduction to the creation and manufacture of effective dosage forms for drug delivery. It presents its subject following the principles of physical pharmacy, product design, and drug regulations. This tripartite structure allows readers to move from theory to practice, beginning from a firm foundation of physical pharmacy principles, including drug solubility and stability estimation, rheology, and interfacial properties. From there, it proceeds to discussions of drug product design and of harmonizing pharmaceutical design with the regulatory regimens and technological standards of the United States, European Union, and Japan. Readers of the second edition of this book will also find: A glossary defining key terms, extensive informative appendices, and a list of references leading to the primary literature in the field for each chapter; Earlier chapters are expanded, with additional new chapters including one entitled "Biotechnology Products"; Supplementary instructor guide with questions and solutions available online for registered professors; Updated regulatory guidelines including quality by design, design space analysis, process analytical technology, polymorphism characterization, blend sample uniformity, and stability protocols. This book is a useful textbook for graduate students in pharmaceutical sciences, drug formulation and design, and biomedical engineering. In addition, professionals in the pharmaceutical industry, including regulatory bodies, will find it a helpful reference guide.